Implementasi Pasal 45 Perda Kabupaten Bandung Barat No. 4 Tahun 2012 Tentang Kriteria Desa Wisata di Desa Wisata Suntenjaya, Kabupaten Bandung Barat (Studi Kasus Kampung Pasir Angling, Desa Suntenjaya) - Alia Nabilah Putri; Muhammad Nurjaman; Mochammad Rifqi Guevara As-sabieq; Neneng Yani Yuningsih (Yayasan Daarul Huda Kruengmane, 2023)
Suntenjaya Village, which is a tourist village, is developing in order to advance the economy in its area. Suntenjaya Village has more potential especially if it is well developed by the community and government by utilizing the natural resources in Suntenjaya Village. To explore and develop the potential of Suntenjaya Village as a tourism village which can then affect the economy of the community which will increase. To see the implementation of Article 45 of the Regional Regulation of West Bandung Regency No. 4 of 2012 concerning Tourism Village Criteria, a comprehensive study of the relationship between Suntenjaya Village as a Tourism Village and Article 45 of the Regional Regulation of West Bandung Regency is needed. Based on the above, this research aims to examine the suitability of Suntenjaya Village as a Tourism Village based on Article 45 of the West Bandung Regency Regional Regulation so that it can be seen whether Suntenjaya Village is in accordance with the criteria mentioned in the article or not. The approach that our group used was a descriptive qualitative method to examine aspects of availability in Suntenjaya Village. The results of the research conducted show that Suntenjaya Tourism Village, in the implementation of government law, has proven to be in accordance with the criteria for tourist villages in accordance with article 45 of the Regional Regulation of West Bandung Regency No. 4 of 2012 concerning Tourism Village Criteria. The results also show that the implementation of this law can encourage residents' income from the agricultural sector and economic activities, which according to the results of our field study has happened in Suntenjaya Village, where the community's economy is helped by the agricultural sector and also the tourism sector.